Ұшқан қаласында жүргізілген жұмыстар (2021 жылғы археологиялық барлау қорытындысы бойынша) (Journal of history-rus, 2023)
The article presents studies of the medieval city of Ushkan, a monument of the culture of settlement. The authors give new conclusions about the city based on data collected in recent years. It is based on the analysis of legends and data.The reason for the formation of cities and settlements in the West Kazakhstan region is the presence of mainly desalinated water sources and trade routes. In connection with active research in recent years, previously little-studied places have been carefully studied. One of them is the city of Ushkan. Studies show that Ushkan was one of the cities with a socio-political foundation in the Middle Ages. During the Golden Horde period, the city was located on the Silk Road, a branch of the caravan route connecting Europe and Asia. Thanks to the transit trade, the city prospered rapidly. The city with underground freshwater springs in the vicinity was of particular importance for the western region with a shortage of water. The city developed, serving merchants.There were no full-fledged archaeological excavations in the city, so written data and reports of ethno-archaeological research were used. If excavations are carried out in the city in the future, we hope that these studies will provide new data. At the same time, an analysis of various assumptions about the origin of the name of the city was carried out. These issues will be outlined in the article.Keywords: Ushkan, archaeological research, city, settled culture, Golden Horde, caravanserai.